1982
DOI: 10.3109/00365528209182037
|View full text |Cite
|
Sign up to set email alerts
|

Morphological Fatty Changes and Function of the Liver, Serum Free Fatty Acids, and Triglycerides During Parenteral Nutrition

Abstract: Morphological fatty changes and function of the liver and serum free fatty acids and triglycerides were investigated in 37 catabolic patients (22 men, 15 women) given different parenteral nutrition regimens. In the glucose group energy was supplied as carbohydrate alone, in the lipid group as carbohydrates and fats, and in addition both groups received amino acids. In the amino acid group amino acids were given in excess and less energy was supplied as carbohydrates. Each patient served as his own control. Dur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
34
0
1

Year Published

1984
1984
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(37 citation statements)
references
References 18 publications
2
34
0
1
Order By: Relevance
“…A carbohydrate rich but fat deficient diet may predispose to fatty liver as surplus carbohydrate induce adipogenic genes [135] . This could well explain the fatty liver, which follows total parenteral nutrition [136] . The classification of fatty liver is summarized in Table 1.…”
Section: Transient Fatty Livermentioning
confidence: 94%
“…A carbohydrate rich but fat deficient diet may predispose to fatty liver as surplus carbohydrate induce adipogenic genes [135] . This could well explain the fatty liver, which follows total parenteral nutrition [136] . The classification of fatty liver is summarized in Table 1.…”
Section: Transient Fatty Livermentioning
confidence: 94%
“…One of the most frequent is hepatic dysfunction (2), especially in infants (3). Liver dysfunction may be manifested by biochemical disturbances such as hyperammonemia (4), elevations in serum transaminases and alkaline phosphatase (5), cholestasis (3), and hepatomegaly, usually as a result of fatty infiltration (6). In a few cases fibrosis (7) and cirrhosis (8) have occurred.…”
Section: Introductionmentioning
confidence: 99%
“…This effect, along with the enhanced catabolism of fatty acid and the attenuated synthesis of fatty acid in the liver when lipid supplementation was provided, strongly suggests that calories in this form should reduce the hepatic steatotic complications. Biopsy studies in man suggest that hepatic steatosis is reduced when lipid emulsions provide a substantial proportion of the calories in TPN regimens (6,12). Animal experiments have indicated that the TPN regimens likely to cause the least steatosis provide -25% of the nonprotein calories as lipid (50).…”
Section: Introductionmentioning
confidence: 99%
“…Studies of patients receiving TPN with hepatic enzyme abnormalities reveal that fatty liver is the most common histologic finding. 97 A poor correlation exists between the degree of fatty change and hepatic enzyme abnormalities. 98 As with other cases of nonalcoholic fatty liver, fatty change from TPN is thought to be a benign, nonprogressive condition that reverses after the prompt cessation of TPN.…”
Section: Tpnmentioning
confidence: 99%
“…However, plasma free fatty acids and triglycerides become characteristically elevated during TPN, which is consistent with an impairment in the action of insulin. 97 Experimental evidence exists that suggests insulin resistance occurs during TPN. 104 Thus, the metabolic profile of hyperinsulinemia, insulin resistance, hypertriglyceridemia, and high levels of plasma free fatty acids seen during TPN resembles that seen in type II diabetes mellitus.…”
Section: Tpnmentioning
confidence: 99%